Formation of 1D "perovskitoid" (API)2Pb3Br10 instead of layered <110> oriented 2D-perovskite (API)PbBr4 under different dissolution temperatures - Wong, Walter Pei De (2025)
The corrugated <110> oriented layered metal halide perovskites (MHP) are gaining increased attention for a variety of properties including intrinsic white light emission. One prototypical candidate is 1-(3-aminopropyl)imidazole lead bromide, which was reported to crystallize as the <110> oriented perovskite (API)PbBr4 [API = 1-(3-aminopropyl)imidazole]. This work shows that under similar reaction conditions, the same components can instead form (API)2Pb3Br10, which has a "perovskitoid" structure. (API)2Pb3Br10 exhibits a reversible phase transition between 60 and -20 °C from a polar space group I2 to a centrosymmetric space group P1¯. The structures and properties of both phases have been characterized by single-crystal and powder X-ray diffraction (XRD) and solid-state nuclear magnetic resonance (ssNMR) accompanied by variable-temperature optical absorption and photoluminescence. In addition, a thermal decomposition of (API)PbBr4 into (API)2Pb3Br10 has been observed between 250 and 300 °C.